Syllabification of Balinese Words Using the Syllabification Algorithm - Putra, Gede Bagus Prawira; Sanjaya ER, Ngurah Agus (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2019)
Abstract This research discusses the syllabification of Balinese words. The syllabification of Balinese words is necessary in determining padalingsa in pupuh. In order to be able to develop the application of technology in the field of pupuh literary, a system that can automatically find the correct division of a Balinese word into syllabels is required. Several studies have been conducted on the syllabification Spanish and Sinhala language using rule-based approach. Both of the studies achieved good accuracy score. Thus, in this research we apply the rule-based syllabification approach on Balinese words. The data used in this study were 257 Balinese words in which the system managed to correctly divide the word as many as 244 and obtained an accuracy score of 94.94%. Keywords: Syllabification Algorithm, Word, Balinese, Word Syllabification, Rule-based